Crescimento e desenvolvimento de alfafa (Medicago sativa L) com diferentes níveis de dormência e frequências de desfolhação contrastantes - Hoppen , Sarah Maria (2021)
The interval between defoliations is one of the factors with the greatest impact on the nutritive value and persistence of pastures; it has an influence on the plant's efficiency in converting light, water and nutrients into photosynthetically active tissue and organic reserves. The aim of this research was quantifying the effects of defoliation frequencies on three dormancy levels of lucerne over five years. The dormancy levels were selected by their physiological differences of perennial reserves in response to external factors, as photoperiod and temperature. Whereas the defoliation frequencies were performed aiming the different stress caused. This study was carried out at the Lincoln University experimental area, in Canterbury, New Zealand, from 2015 to 2019. The experimental design was in blocks, with three main plots (defoliation frequencies – CF); three sub plots (fall dormancy genotypes – FD) and four replications. The defoliation frequencies were at every 28 days (CF 28), every 42 days (CF 42) and every 84 days (CF 84), in genotypes FD2 (AgR Palatable), FD5 (Grassland Kaituna) and FD10 (SARDI 10), resulting in 9 treatments. The analyses consisted in aerial and perennial harvesting to agronomical variables determination, physiological and nutritional; as non-destructive evaluations that aimed the canopy development comprehension over the regrowth process. The defoliation frequencies were efficient in generate different carbon (C) limitations, resulting in lower shoot yield (average of 7.5 t DM ha-1 year-1), greater intensity of plant population reduction, lower leaf area index (LAI) in plants submitted to CF 28. These differences were the result of photossynthetically active radiation intercepted (PARi) of this treatment (593.3 MJ m-2 year-1, 1050.5 MJ m-2 year-1 and 1415.9 MJ m-2 year-1 at CF 28, CF 42 and CF 84, respectively) that reduced the total radiation use efficiency (RUEtotal), and demanded greater mobilization of perennial reserves to shoot regrowth. Contrary, the CF 84 caused greater leaf senescence and the plant inlet in reproductive phase due to the low defoliation frequency, which reflected on LAI and leaf:stem ratio reduction, with direct impact on nutritional quality decrease. The damage was cumulative over the study period, which caused collapse signals on all genotypes canopies under CF 28, however with different intensities. Among the dormancy levels, the FD2 and FD5 showed greater partitioning to perennial organs capacity that resulted in the increase of these organs biomass yield and greater water and nutrients absorption, which impelled greater energy support to a faster canopy expansion. Though the FD10 plants naturally present greater LAI and shoot height, these advantages were annulled over the years, by the lower regrowth capacity that leaded to a more intense reduction of plant survival and, consequently, shoot yield. The C limitations were accompanied by nitrogen (N) limitation, empowered by the low water availability and lower perennial development in less dormant plants. It has been concluded that the FD2 CF 42, under that environment, are the most indicated to Canterbury region, as the most efficient in the interception, use and partitioning of N and water.